STORYBOOK “GUARDIÕES DA SAÚDE” - Elvys Wagner Ferreirada Silva; Karla Jeane Coqueiro Bezerra Soares; João Aranha Barros; Welberth Santos Ferreira (REVISTA DE ESTUDOS INTERDISCIPLINARES, 2026)
This article presents the design and analytical process of the storybook Guardians of Health and its complementary material, developed as didactic resources for Science Education in Early Childhood Education. The main objective was to create a multimodal narrative proposal that introduces young children to scientific notions related to the body, health habits, and self-care, integrating imagination, language, and everyday experiences. The methodology adopted followed a qualitative instructional design approach, involving curriculum analysis, theoretical grounding, literary scripting, visual production, development of pedagogical activities, and critical reflection on the educational potential of the material. The resource demonstrates conceptual and aesthetic coherence, supporting the integration of imagination, language, and scientific knowledge in a sensitive, playful, and interdisciplinary manner. The presence of guardian-characters, the temporal organization of the narrative, and the use of multimodal languages contribute to making scientific concepts accessible and meaningful to children. The storybook represents a promising tool for teachers seeking to integrate narrative and scientific literacy in Early Childhood Education, although its effectiveness will depend on future implementation processes, teacher mediation, and contextual analysis. Further work is recommended to validate the material empirically and expand its thematic scope.